Proficient brain for optimal performance: the MAP model perspective - Bertollo, M.; Di Fronso, S.; Filho, E.; Conforto, S.; Schmid, M.; Bortoli, L.; Comani, S.; Robazza, C. (PeerJ, 2016)
Background. The main goal of the present study was to explore theta and alpha event-related desynchronization/synchronization (ERD/ERS) activity during shooting performance. We adopted the idiosyncratic framework of the multi-action plan (MAP) model to investigate different processing modes underpinning four types of performance. In particular, we were interested in examining the neural activity associated with optimal-automated (Type 1) and optimal-controlled (Type 2) performances.